Self‐Assembly of PEG‐Coated Ceria Nanoparticles Shows Dependence on PEG Molecular Weight and Ageing. Issue 11 (16th July 2015) - Neal, Craig J.; Das, Soumen; Saraf, Shashank; Tetard, Laurene; Seal, Sudipta
Abstract: Cerium oxide (ceria) nanoparticles (CNPs) were synthesized in poly(ethylene glycol)s (PEGs) of different molecular weights (MWs; 300, 600, 1500, 3000, 4000, and 6000 Da) with water as a cosolvent, and changes in physicochemical properties, especially morphology and size, were monitored as a function of time. High‐resolution transmission electron microscopy (HRTEM) was performed for all solutions and revealed octahedral, star morphologies for CNPs coated with 1500 MW PEG. Raman and FTIR spectroscopy, HRTEM images, conductivity, and electrophoretic mobility imply the self‐assembly of small spherical particles to octahedral, star‐shaped particles by means of a fractal assembly method. Dynamic light scattering measures were used to create an empirical growth model of the observed octahedral self‐assembly. It was also determined that PEG polymer chain lengths and age‐dependent redox activities of CNPs limit or allow this assembly owing to molecular‐weight‐dependent physicochemical properties. This study highlights the significance of ageing on solution‐based nanoparticles and its implications in the use of nanoparticles over long periods of time. As PEG‐ylated nanoparticles have found extensive use in biomedical applications, we have tested the aged particles in vitro for toxicity. Abstract : Pull yourself together : Age‐dependent self‐assembly of cerium oxide nanostructures results in different structures from different chain lengths of poly(ethylene glycol) through hydrogen‐bonding and electrostatic interactions (see scheme). Increasing chain length produces increased hydrophobicity and increased chain flexibility. Chain coiling and intramolecular bonding also influence the ability of particles to self‐assemble.